Disagreement - Feldman, Richard, 1948-; Warfield, Ted A., 1969- (Oxford : Oxford University Press, 2010)
Disagreement is common: even informed, intelligent, & generally reasonable people often come to different conclusions when confronted with what seems to be the same evidence. Can the competing conclusions be reasonable? If not, what can we reasonably think about the situation? This book covers the epistemology of disagreement.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Knowledge, Theory of; Verbal self-defense -- Philosophy; Compromise (Ethics); Dogmatism -- Philosophy